Effect of a mutation in the anticodon of human mitochondrial tRNAPro on its post-transcriptional modification pattern. - Brulé, H (1998)
Although the gene sequences of all 22 tRNAs encoded in the human mitochondrial genome are known, little information exists about their sequences at the RNA level. This becomes a crucial limitation when searching for a molecular understanding of the growing number of maternally inherited human diseases correlated with point mutations in tRNA genes. Here we describe the sequence of human mt-tRNAPropurified from placenta. It shows absence of editing events in this tRNA and highlights the presence of eight post-transcriptional modifications. These include T54, never found so far in an animal mt-tRNA, and m1G37, a modification known to have fundamental functional properties in a number of canonical tRNAs. Occurrence of m1G37 was further investigated in an analysis of the substrate properties of in vitro transcripts of human mt-tRNAProtowards pure Escherichia coli methylguanosine transferase. This enzyme properly methylates G37 in mt-tRNA and is sensitive to the presence of a second G at position 36, neighboring the target nucleotide for methylation. Since mutation of nt 36 was shown to be correlated with myopathy, the potential consequences of non-modification or under-modification of mt-tRNA nucleotides in expression of the particular myopathy and of mitochondrial diseases in general are discussed.